Post-Executive Order 13583: a Reexamination of Occupational Barriers in Federal Law Enforcement - Yu, Helen H. (Women & criminal justice, 2017)
This study examined occupational barriers in federal law enforcement between 2011 and 2015, replicating research conducted prior to the passage of Executive Order 13583 (2011). Qualitative and quantitative data were generated from surveys collected from 101 sworn female federal law enforcement officers on the challenges they face in the work environment. With little progress to gender equity, findings revealed that male colleagues’ resistance to women in federal policing and the perceived lack of promotions has increased, while work-life balance policies and sexual discrimination continue to be a challenge. Policy implications for improving organizational practices are discussed.